Kreativität grenzenlos!? inner- und außerschulische Expertisen zu inklusiver Kultureller Bildung - Henning, Ina; Sauter, Sven 1963-; Witte, Katharina 1971- (Pädagogik, 2019)
Active participation in culture and the arts for everybody - an overview of existing approaches of inclusive cultural education